USE OF FACTORIAL DESIGN IN THE TESTS OF CONTROLLED ACID RELEASE 1,3 INDOLACETIC LOADED IN QUITOSANE MATRICES - Valderrama Negrón, Ana (2017)
In this work we used the factorial design of experiments for the preparation of chitosan particles loaded with the vegetable hormone 1,3-indoleacetic acid (AIA) to study its controlled release in water. The chitosan particles were prepared by dissolving the hormone and chitosan in acetic acid and then dripping in NaOH solution with constant stirring. Factorial Design 23 was used to study the concentration of chitosan (% chitosan), gelation time in NaOH (time in NaOH) and sodium tripolyphosphate (TPP) concentration (% of TPP). In response, the amount of hormone released in 2 hours, measured spectrophotometrically at 285 nm, was obtained. The results of the experimental design indicated that the three factors influence the released amount of AIA in 2 hours, where a higher concentration of chitosan increases the rate of release, while the higher concentration of TPP and longer gelation time in NaOH decreases the release rate.